Development of Green Chemistry-Based Practicum Module for Senior High School to Promote Students’ Environmental Literacy - Noer Kurnia Dewi; Risnita Vicky Listyarini* (Jurnal Pendidikan Sains Indonesia, 2022)
Chemistry learning ideally should invite students to interact directly with the object being studied. This can be realized through a practicum in the laboratory. However, chemistry practicum still generates significant waste in the environment. There is also a need for character education to promote environmental literacy. Therefore, there is a need for a green chemistry-based practicum module for class X senior high school. This research aims to develop a green chemistry-based practicum module, to know the quality of a green chemistry-based practicum module, and to know the students' responses to environmental literacy. This a research and development using a modified Borg and Gall development model that includes information gathering, planning, product development, limited trial, and product revisions. The results of the validity of the green chemistry-based practicum module in terms of material had a percentage of 93.45% and in terms of media had a percentage of 90.00% with a very valid criterion. The use of the green chemistry-based practicum module gets a very practical criterion with a score of 86.67% based on students’ responses. The green chemistry-based practicum module effectively increases students’ learning outcomes which are marked by the n-gain value of 0.3 - 0.78 in the medium to high criteria. The value of tcount ttable and sig.(2-tailed) in three practicums 0.05 indicates that the green chemistry-based practicum module can support students' environmental literacy